2022
DOI: 10.3390/ijms231911640
|View full text |Cite
|
Sign up to set email alerts
|

Yeast-Fermented Rapeseed Meal Extract Is Able to Reduce Inflammation and Oxidative Stress Caused by Escherichia coli Lipopolysaccharides and to Replace ZnO in Caco-2/HTX29 Co-Culture Cells

Abstract: (1) The present study tested in vitro the capacity of a fermented rapeseed meal extract to reduce medicinal ZnO, which will be banned at the EU level from 2023 onwards because of its potential to cause environmental pollution and the development of Zn resistance in gut bacteria. Rapeseed meal could be an important ZnO substitute as it has antioxidant/radical scavenging properties due to its content of bioactive compounds (e.g., polyphenols). (2) Protein array and flow cytometry were used to detect apoptosis, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…These results suggest that the regulation of PKCOS on the mRNA expression of TNF-α and CASP3 may result from multi-target genes and play a protective role in the LPS-induced apoptosis of IPEC cells. Similar to the other oligosaccharides obtained from plant/food/feed reported by other researchers [58], PKCOS presented anti-inflammatory effects through downregulating the expressions of target genes associated with cell death, such as CASP3 and TNF-α.…”
Section: Discussionsupporting
confidence: 77%
“…These results suggest that the regulation of PKCOS on the mRNA expression of TNF-α and CASP3 may result from multi-target genes and play a protective role in the LPS-induced apoptosis of IPEC cells. Similar to the other oligosaccharides obtained from plant/food/feed reported by other researchers [58], PKCOS presented anti-inflammatory effects through downregulating the expressions of target genes associated with cell death, such as CASP3 and TNF-α.…”
Section: Discussionsupporting
confidence: 77%
“…Previous research has demonstrated that substituting soybean meal with fermented canola meal leads to a significant elevation in serum CAT activity and a notable reduction in MDA levels ( P < 0.05) in growing pigs ( 31 ). Additionally, there is evidence suggesting that fermented rapeseed meal extracts are capable of mitigating oxidative stress ( 33 ). The marked divergence between the outcomes of these studies and our own may stem from the fact that the mixed meal utilized in our experimental design was not subjected to a fermentation process.…”
Section: Discussionmentioning
confidence: 99%
“…A significant phenolic component in rapeseed meal is sinapine, which accounts for up to 80% of all phenols and is known for its robust antioxidant properties (Liu et al, 2023). The mechanism of polyphenols in antioxidative defense primarily involves scavenging reactive oxygen species, such as hydroxyl and superoxide radicals (Zhao et al, 2021), and chelating transition metal ions like Fe +2 , which are known to generate free oxygen radicals (Taranu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%